17 EdTech Frameworks and Who Needs to Know Them - Bapna, Akanksha; Nicolai, Susan; Myers, Christina; Pellini, Arnaldo; Sharma, Namrata; Wilson, Sam; Wilson, Susan Nicolai, Christina Myers, Arnaldo Pellini, Namrata Sharma and Sam, Akanksha Bapna (EdTech Hub, 2021)
17 EdTech frameworks that provide a valuable bridge between theory and practice. EdTech resources for policy-makers, educational institutions, teachers and multi-stakeholders.
KerkoCite.ItemAlsoKnownAs: 2339240:ZT8D763J 2405685:9TG8YM2I

A Case for a Systems Approach to EdTech - Bapna, Akanksha; Nicolai, Susan; Myers, Christina; Pellini, Arnaldo; Sharma, Namrata; Wilson, Sam (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 5651995 previousDOI: 10.5281/zenodo.4604769 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4604769 10.5281/zenodo.5651995 2339240:5JZ4FURY 2339240:5MG5JK99 2339240:8CEUGJ7E 2339240:N7XVM2BS 2339240:QL5LSA92 2339240:UIDN49MT 2405685:5HSPDN5N 2405685:AMGEVSIH 2405685:JMP2BJ2E 2405685:M8P5BVVK 2405685:ST8IBIUV 2405685:UR6CQL9K 2405685:VBZ4N4AM 2534378:PDNLLG9Y 4656463:RA69ZQLB
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _r:AddedByZotZen; _zenodo:submitted

A Country-Level Research Review: EdTech in Tanzania - Jordan, Katy; Proctor, Jamie; Koomar, Saalim; Bapna, Akanksha (Zenodo, 2021)
This document presents a review of the research landscape in Tanzania in relation to EdTech research focused on learners, teachers, or systems at the level of school-based education, excluding higher education (HE). The review draws upon the research literature, policy documents, grey literature, and interviews with key stakeholders in order to present an overview of the research landscape in Tanzania. There is a substantial body of relevant EdTech research which has been undertaken in Tanzania in the past decade. Eighty research articles were identified for inclusion in the review. This document provides an overview of trends in this literature and key actors and projects, and provides a specific focus upon existing research which relates to EdTech Hub’s ‘high-potential evidence gaps’ (HPEG) framework. In combination with political economy analysis, three areas for future research which would be practical and likely to have high impact are identified and described.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4618376 10.5281/zenodo.5652060 2339240:F8ER2X27 2339240:KZ7L8K2X 2339240:YKGMJASP 2405685:3F4ASVFA 2405685:IA77HHMV 2405685:RQGJRKVS 2405685:TYZ4Y65R 2405685:VRE5DB5K
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodoETH

Country-Level Research Review: EdTech in Kenya - Myers, Christina; Kaye, Tom; Bapna, Akanksha; Williams, Ayesha; Mitchell, Joel (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5256847 2405685:FQP8MJIY 2405685:SNBW6BK6
Keywords: _DOILIVE; _r:AddedByZotZen; _zenodo:submitted

Raising readers: Kenya schools use of technology to improve parent and carers' engagement in literacy learning: Inception Report - Nicolai, Susan; Zubairi, Asma; Bapna, Akanksha; Myers, Christina (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5784255 2405685:ZT3TGJ26
Keywords: _r:AddedByZotZen